Characterizations of Contra-$(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new class of functions between bitopological spaces, namely contra-$(τ_1,τ_2)$-continuous functions. Furthermore, several characterizations and some properties concerning contra-$(τ_1,τ_2)$-continuous functions are investigated.